Carbon Transfer Processes of Food Web and Trophic Pathways in a Tropical Eutrophic Seagrass Meadow - Cui, Lijun; Jiang, Zhijian; Huang, Xiaoping; Wu, Yunchao; Liu, Songlin; Chen, Qiming; Li, Jinlong; He, Jialu (Frontiers in Marine Science, 2021)
Seagrass meadows provide important habitats and rich organic carbon sources for consumers of different trophic levels but are threatened by accelerating eutrophication in coastal waters. Nevertheless, the carbon transfer processes throughout the food web and trophic pathways in the eutrophic seagrass meadows are still poorly known at present. To resolve this issue, the carbon sources of different trophic communities in a eutrophic tropical seagrass meadow (Xincun Bay, South China Sea) under eutrophication were examined in summer and winter using dual stable isotopes. The δ13C values of omnivores and carnivores overlapped more with that of herbivores and planktivores/filter feeders, which mainly overlapped with that of epiphytes in summer and macroalgae in winter. Meanwhile, epiphytes and macroalgae exhibited high biomass and the corresponding highest contribution to herbivores, omnivores, and carnivores in summer and winter, respectively. These results suggest that the grazing food chain was the main trophic pathway in this eutrophic seagrass meadow, and the transfer of carbon flow in the grazing food chain was mainly dominated by the proliferated epiphytes or macroalgae carbon. In contrast, the contribution of seagrass to detritivores in both seasons was higher than that of other food sources. Our findings suggest that, in eutrophic tropical seagrass meadows, the proliferation of epiphytes or macroalgae induced by high nutrient loading, as well as their seasonal changes have a greater impact on the transfer of carbon in the grazing food chain than that in the detritus food chain, and seagrass fueled the food web mainly through the detritus food chain.